EFFECTS OF OBESITY ON PREGNANCY AND ITS OUTCOME: Effects of Obesity on Pregnancy - Choudhry, Humaira; Choudhry, Abeera; Azam, Naila; Jan, Shahida (Pakistan Armed Forces Medical Journal, 2009)
Objective: The objective of study was to find out adverse effects of obesity on pregnancy. Study Design: A case - control study comparing outcome of pregnancy in obese women with a control group of non obese. Place and Duration of Study: Obstetrics unit of Military Hospital Rawalpindi from 20th December 2004 to March 2006. Subjects and Materials: The study included 100 obese ladies with body mass index (BMI) 28-35 and 100 non obese ladies with BMI 18-25 Results: Pregnancy in obese women associated with increased risk of complications. These women had a higher frequency of pregnancy-induced hypertension (RR  1.75; 95% CI  1.08 – 2.81) and gestational diabetes mellitus (RR  3.0 ; 95% CI  1.13 – 7.94), a higher cesarean section rate (RR 1.78 ; 95% CI  1.91 – 2.67) , increase in postpartum hemorrhage (RR  3.50; 95% CI  1.19 – 10.27) and higher babies weight (RR  2.83; 95%  CI 1.50 – 5.15). Conclusion: This study concluded that obes woman were at high risk of antepartum, intrapartum and postpartum complications with an increased risk of operative delivery.